Identifikasi Morfologi Jamur Penyebab Penyakit Busuk Tandan Kelapa Sawit dan Uji Konsentrasi Kitosan Terhadap Jamur Tersebut Secara in Vitro - Yetti Elfina; Irfandri; Aisyah Sabirunah; Dimas Wijayanto; Herhadi Solihin; Iswandi; Rizki Bintang Ramadhan Harahap (Universitas Sam Ratulangi, 2024)
Fruit bunch rot disease on oil palms can cause a decrease in oil palm productivity in Riau Province. An alternative to controlling oil palm bunch rot disease can be using an organic fungicide, namely chitosan. Research aims to identify the causes of oil palm bunch rot disease and test the effect of chitosan concentration in inhibiting this fungus in vitro. The treatments in this study were several concentrations of chitosan (K) consisting of: K0 = Chitosan 0 g.l-1; K1 = Chitosan 2.5 g.l-1; K2= Chitosan 5 g.l-1; K3 = Chitosan 7.5 g.l-1; K4 = Chitosan 10 g.l-1. The chitosan application was analyzed statistically using variance based on the F test at the 5% level using the SPSS application. Research results The cause of oil palm bunch rot disease in Pongkai Village, District XIII Koto Kampar, Kampar Regency, Riau is Marasmius palmivorus based on its morphology. Providing concentrated chitosan able to inhibit the growth of Marasmius palmivorus in vitro. Chitosan concentrations of 2.5 g.l-1, 5 g.l-1, 7.5 g.l-1, 10 g.l-1 able to inhibit the growth of the fungus Marasmius palmivorus with respective inhibitions of 36.52%, 45.68%, 50.55 %, 64.16%, The higher the chitosan concentration, greater the inhibition of fungal growth that occurs.